The Socio-Economic Impact of the Construction of the Suramadu Bridge on the People of Bangkalan, Madura (Case Study: Tangkel Highway) - Raudhatul Mustaqimah; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
The construction of the Suramadu Bridge (Surabaya-Madura) connecting the islands of Java and madura has brought major changes to the economic and social dynamics of the Madurese community, especially in Bangkalan Regency. This study aims to analyze the economic and social impacts of the construction of the bridge on the community around Jalan Raya Tangkel, which is the main route connecting to the interior of Madura. Using a qualitative descriptive approach, with the focus of the study 1. The impact of the construction of the Suramadu Bridge on the socio-econmic sector og Jalan Raya Tangkel 2. The impact of the Suramadu regional development policy. The results of the study indicate that the construction of the bridge has increased community mobility, expandedmarket acces, and grown local economic activities,especially the informal sector and medium enterprises. However, negative impacts were also found such as increasing social inequality, changes in local cultural values, and conflicts related to land ownership and spatial planning. This study concludes that the construcyion of large infrastructure such as the Suramadu Bridge muat be balanced with policies that facor local communities so that the benefits can be felt evenly and sustainably.